The Influence of supplier relationship management practices on operational performance of large manufacturing organizations in Kenya - Kiarie, Joyce Wairimu (Strathmore University, 2017)
With the advent of the world as a global village, the supply chain has not remained immune to the sweeping changes that are taking place; the key paradigm that has been affected in the management of the supply chain is the aspect of supplier relationship management. The main objective of this study was the identification of the influence of supplier relationship management practices on organizational performance the case being large manufacturing firms in Kenya with the specific objectives being three: firstly, the identification of the supplier relationship management practices used, secondly, an exploration of the effects of the supply chain attributes and finally the determination of the challenges of supplier relationship management. The large manufacturing firms are here defined as those that have turnover revenue of 100 million, or over 500 employees or more or having more than one branch. The study adopted the use of correlational and descriptive research design while the population consisted of 594 listed manufacturing firms in Kenya according to the Kenya Association of Manufacturers. Out of the population, a sample size was selected (60) through simple probability sampling more specifically simple random sampling which was a representative figure of the whole population. The data collection instrument was a structured questionnaire that had both open ended and close ended questions. Data was analyzed through the use of qualitative and quantitative methods and presented in form of tables, graphs and charts as well as summary based on thematic areas. The regression analysis findings show that 64.6% of variations in firm operational performance are explained by variations in Supply relations management practices and 85.5% of variations in firm operational performance are explained by variations in the supply relationship management practices and supply chain attributes, Through this finding the study concludes that there is a relationship between the dependent and independent variables as well as the moderating variables that are supply chain attributes. The study further recommends the benefits that can be accrued from SRM practices deserve a strategy so as to impact positively on operational performance. Among the conclusions of the study are: SRM was highlighted to have significant effect on operational performance of manufacturing organizations.
Thesis submitted in partial fulfillment for the requirements for the Degree of Master of Commerce (MCOM) at Strathmore University
Keywords: Manufacturing Organizations; Manufacturing Firms; Supplier Relationship Management Practices; Supplier Relationship Management